35 INCREASED UTILIZATION AND COST OF DRUG-ELUTING STENTS IN CONTEMPORARY PRACTICE. (1st March 2005) - Senter, S. R.; Nathan, S.; Bhatt, P.; Gupta, A.; Calvin, J.; Klein, L. W.
Abstract : Background: Although evidence-based recommendations for drug-eluting stents (DES) are well known, an understanding of actual utilization in contemporary practice is limited. Methods: Between April 2003 and May 2004, a total of 219 consecutive cases of DES to treat 252 lesions in 205 patients were compared to 3 evidence-based categories (refer to graphic). Procedure costs were determined by ratio of cost-to-charges and the incremental cost for DES equal to $2000. Results: Patients were predominantly male (72%), with a mean age of 63 ± 11 years; 38% were diabetic, 18% had MI within the last 30 days, and 22% had prior CABG. Most cases were elective (94%), but 34% (94/277) of DES were deployed in less favorable lesions: 10% bifurcation, 7% chronic total occlusion (CTO), 7% saphenous vein graft (SVG), 6% in-stent restenosis (ISR), and 3% ostial. Per case, 1.3 ± 0.5 DES were used: 76% (161/219) had 1 DES, 20% (43/219) had 2 DES, and 4% (8/219) had 3 DES. Over 1 year, each patient received 1.4 ± 0.5 DES with a mean length of stay of 2.0 days. In contemporary practice, 62% of DES were used outside of Level A recommendations at an incremental cost of $1714. Conclusions: The use of DES in contemporary practice differs significantly from current evidence-based recommendations, resulting in significantly increased utilization and cost. Further investigation is needed substantiate the benefit of DES, decreased restenosis, in these subgroups. (Figure )